A Randomized, Double‐Blind, Placebo‐Controlled, Sixteen‐Week Study of Subcutaneous Golimumab in Patients With Active Nonradiographic Axial Spondyloarthritis. Issue 10 (23rd September 2015) - Sieper, J.; van der Heijde, D.; Dougados, M.; Maksymowych, W. P.; Scott, B. B.; Boice, J. A.; Berd, Y.; Bergman, G.; Curtis, S.; Tzontcheva, A.; Huyck, S.; Weng, H. H.
Abstract : Objective: Axial spondyloarthritis (SpA) is a chronic inflammatory disease characterized by back pain and stiffness. The objective of this study was to determine whether golimumab is superior to placebo in patients with nonradiographic axial SpA. Methods: This phase III, double‐blind, randomized, placebo‐controlled trial was performed to evaluate subcutaneous golimumab (50 mg) versus placebo in patients ages ≥18 years to ≤45 years who had active nonradiographic axial SpA according to the Assessment of SpondyloArthritis international Society (ASAS) criteria for ≤5 years since diagnosis, high disease activity, and an inadequate response to or intolerance of nonsteroidal antiinflammatory drugs. Patients were randomized 1:1 to receive golimumab or placebo subcutaneously every 4 weeks. The primary end point was 20% improvement according to the ASAS criteria (ASAS20) at week 16. Key secondary end points were an ASAS40 response, ASAS partial remission, 50% improvement in the Bath Ankylosing Spondylitis Disease Activity Index (BASDAI), and change in the Spondyloarthritis Research Consortium of Canada (SPARCC) magnetic resonance imaging (MRI) index for sacroiliac (SI) joint inflammation (SPARCC score). Results: Of the 198 patients randomized, 197 were treated (97 received golimumab, and 100 received placebo). The mean age of the patients was 31 years, and 57.1% were male. At baseline, the mean ± SD BASDAI was 6.5 ± 1.5, the mean ± SD ASDAS was 3.5 ± 0.9, and the mean ± SD SPARCC score was 11.3 ± 14.0. The primary end point, an ASAS20 response, was achieved by significantly more patients in the golimumab group compared with the placebo group (71.1% versus 40.0%; P < 0.0001). An ASAS40 response was also achieved by significantly more patients in the golimumab group compared with the placebo group (56.7% versus 23.0%; P < 0.0001). The incidence of adverse events did not differ meaningfully between groups. Conclusion: Patients with active nonradiographic axial SpA treated with golimumab had significantly greater improvement in symptoms compared with patients treated with placebo. Golimumab was well tolerated and had a favorable risk/benefit profile.